2014
DOI: 10.5502/ijw.v4i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Measuring flourishing: The impact of operational definitions on the prevalence of high levels of wellbeing

Abstract: Abstract:The epidemiology of flourishing is an important research topic prompting international interest in its psychometric assessment. But the need to measure human feelings and functioning at the population level has resulted in the creation of a multitude of different conceptual frameworks of flourishing: a term now commonly used to describe high levels of subjective wellbeing. Not only do different researchers theorise and conceptualise flourishing in different ways, but also the categorical diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
241
2
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(284 citation statements)
references
References 26 publications
9
241
2
18
Order By: Relevance
“…In this study, we suggest that rather than simply measuring happiness or life satisfaction, it is more meaningful to attempt to uncover a more holistic measure of wellbeing, which the participants differentiated from happiness. This confirms the conclusions of other researchers (e.g., Hone et al, 2014;Jayawickreme et al, 2012). The findings of the current study can help inform future research on how to measure these constructs in operationalizations that are meaningful for people's daily lives, and to help promote balance and a focus on all parts of life -social, familial, physical, as well as work-related and educational -as a way to promote happiness and wellbeing.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In this study, we suggest that rather than simply measuring happiness or life satisfaction, it is more meaningful to attempt to uncover a more holistic measure of wellbeing, which the participants differentiated from happiness. This confirms the conclusions of other researchers (e.g., Hone et al, 2014;Jayawickreme et al, 2012). The findings of the current study can help inform future research on how to measure these constructs in operationalizations that are meaningful for people's daily lives, and to help promote balance and a focus on all parts of life -social, familial, physical, as well as work-related and educational -as a way to promote happiness and wellbeing.…”
Section: Resultssupporting
confidence: 74%
“…A recent article compared the four extant scales of Keyes (2002), Diener and others (2010), Seligman (2011), and Huppert and So (2013) for measuring flourishing both conceptually and empirically. They found that all four tap into both feeling and functioning, and include positive relationships, engagement or interest, and meaning and purpose (Hone et al, 2014). Each model differs in the other components; however, this study lends "real world" support to the notion that wellbeing does include each of these attributes and cannot be simplified to a hedonistic conception of happiness.…”
Section: Resultsmentioning
confidence: 82%
“…Når flourishingbegrepet brukes på denne måten, inkluderer det gjerne wellbeingkomponenter utover dem som vanligvis kategoriseres som eudaimoniske. Framstillingen videre, saerlig presentasjonen av perspek tivene til Keyes (2005Keyes ( , 2013 Hone et al (2014) kommenterer at det så langt bare er Keyes' teoretiske rammeverk som har vaert gjenstand for omfattende empirisk validering, og at bruk av operasjonaliseringer av de tre andre modellene fører til temmelig ulike resultater. Følgelig bør bruk av flourishingmål i indikator sammenheng foretas med varsomhet.…”
Section: Begrepet «Flourishing» Har Filosofiske Røtter I Den Aristoteunclassified
“…There also must initially be zero power Just as there is no accepted model of collaboration, there is also no accepted definition of wellbeing nor an associated survey instrument. Hone, Jarden, Schofield, and Duncan [72] nominated four wellbeing instruments (see Table 2 below) that, when considered in conjunction, demonstrate substantial overlap with PILAR and positive psychology. The overlap is extended by inclusion of the initial condition assumed by PILAR, termed idealised collaboration [32].…”
Section: Wellbeing As Antecedent To Psycapmentioning
confidence: 99%